Pengaruh Pendidikan Formal Dan Informal Terhadap Minat Berwirausaha Pada Ukm di Kelurahan Medan Tenggara - Nauval Rachman Siregar; Adelina Lubis; Ahmad Rafiki (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
The purpose of this study was to determine the effect of formal and informal education on entrepreneurial interest in SMEs in the village of Southeast Medan. The population is the owners of SMEs in the village of Southeast Medan, amounting to 66 people. The method of data collection is done by questionnaire. The data analysis method uses data analysis tests, classical assumptions, multiple linear analysis and hypothesis testing. The results showed that formal and informal education simultaneously had a positive and significant effect on interest in entrepreneurship with a value of Fcount (25.496) Ftable (3.14). Formal education partially has a positive and significant effect on interest in entrepreneurship with a significant value of 0.000 0.05 or tcount (5,445) ttable (1,998). Informal education partially has a positive but not significant effect on interest in entrepreneurship with a significant value of 0.230 0.05 or tcount (1,211) ttable (1,998). The Adjusted R Square figure is 0.430 or 43%, which means that the magnitude of the influence of the variables of formal education and informal education on entrepreneurial interest is 43% while 57% is explained by other variables not examined in this study.